Microvillus Inclusion Disease Associated with Necrotizing Enterocolitis in a Premature Infant - Sayar, Ersin; Kalay, Salih; Yilmaz, Aygen; Oztekin, Osman; Islek, Ali; Elpek, Gulsum Ozlem; Kalay, Zuhal; Tezel, Gonul; Artan, Reha (American Journal of Perinatology Reports, 2014)
Microvillus inclusion disease is one of the congenital diarrheal disorders characterized by the appearance of inclusion bodies on the intestinal epithelium. To date there are a few cases and also a few other associated finding reports related to this life-threatening disease in literature. In this report, we present a premature infant with microvillus inclusion disease that was associated with necrotizing enterocolitis. Thus, we should be aware of the appearance of necrotizing enterocolitis in patients with microvillus inclusion disease, especially when contributing factors are present.
Keywords: microvillus inclusion disease; intractable diarrhea; necrotizing enterocolitis; premature